SERVICE QUALITY, SATISFACTION, AND LOYALTY ON PATIENT DENTAL HOSPITAL OF JEMBER UNIVERSITY - Satar; Diah Yulisetiarini; Hendriyono (Program Studi Ilmu Keperawatan Universitas Jember, 2016)
Business competition is now entering the era of high competition. The company has always tried to maintain maximum customer who has achieved. Various methods through excellent service, competitive prices, indirect aspects such as brand image with the purpose of providing satisfaction to customers through the services or products offered. This research is explanatory or confirmatory or testing the hypothesis that explains the influence or causal relationships between variables through hypothesis testing. This study describes the relationship between the exogenous variables (quality of service), endogenous intervening (satisfaction), and the endogenous variables bound (loyalty). The relationship between these variables is described in the structural relationships directly or indirectly, partially or simultaneously. The study population includes outpatient clinics oral surgery, dental conservation, prosthodontics, perio and oral medicine at the Hospital University of Jember. The sample size of 120 people were taken to the cluster and purposive technique. This study using path analysis or flow charts. Then make equation modeling and analysis include: 1) designing a model based on the theory; 2) prepare the path diagram; 3) change the path diagram into a structural equation; 4) selecting an input matrix for data analysis; 5) assess the model identification; 6) evaluating the model estimation; 7) the interpretation of the model. There is a direct effect of service quality on satisfaction (0.215). The direct effect of service quality on loyalty (0.290). The direct effect of satisfaction on loyalty (0.636). There is no direct influenceon the quality of service loyalty (0,447). There are a total effect of service quality on satisfaction (0.703). Effect of total quality of service loyalty (0.736). Effect of total satisfaction on loyalty (0.636). Direct effect on the quality of service satisfaction, andsatisfaction effect on patient loyalty Dental Hospital of the University of Jember. Quality of service is not direct effect on patient loyalty Dental Hospital of the University of Jember. Quality of service is the total effect on patient satisfaction Dental Hospital ofthe University of Jember.